2013
DOI: 10.1007/s12185-013-1379-8
|View full text |Cite
|
Sign up to set email alerts
|

Acute exacerbation of Toxoplasma gondii infection after hematopoietic stem cell transplantation: five case reports among 279 recipients

Abstract: Toxoplasmosis is a rare and possibly underestimated complication following hematopoietic stem cell transplantation (HSCT) associated with a high mortality rate, although the incidence of toxoplasmosis after HSCT in Japan has not been established. We retrospectively studied patients with toxoplasmosis after HSCT, and identified five patients who had been diagnosed with an acute exacerbation of toxoplasmosis among 279 HSCT recipients at our institution between 1998 and 2011, representing an incidence of 1.8 %. A… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
36
0
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(38 citation statements)
references
References 20 publications
1
36
0
1
Order By: Relevance
“…In 67 cases (19%), the toxoplasma serostatus pre-HCT was unknown. These findings are consistent with several observational studies demonstrating a higher incidence of toxoplasmosis in allo pre-HCTSP vs. allo pre-HCTSN [3,5,6,9,11,[15][16][17][18][19][20][21][22][23].…”
Section: Allo-haematopoietic Cell Transplant Recipientssupporting
confidence: 91%
“…In 67 cases (19%), the toxoplasma serostatus pre-HCT was unknown. These findings are consistent with several observational studies demonstrating a higher incidence of toxoplasmosis in allo pre-HCTSP vs. allo pre-HCTSN [3,5,6,9,11,[15][16][17][18][19][20][21][22][23].…”
Section: Allo-haematopoietic Cell Transplant Recipientssupporting
confidence: 91%
“…Whereas the chronic state is typically asymptomatic in immunocompetent adults, the de novo infection or the activation of latent Toxoplasma infection can cause life-threatening disease in immunocompromised hosts (transplacental infection of the human fetus is not addressed in this paper) [1][2][3] . Acute toxoplasmosis has been reported to occur with a frequency of 2-3% in stem cell recipients [4,5] , with very high mortality rates up to 82% [6] . Clinical symptoms of toxoplasmosis commonly arise within the first 3 months after hematopoietic stem cell transplantation (HSCT), with median onset 2 months after transplantation; less than 10% of cases occur before day 30 and 15-20% of cases 100 days after transplantation.…”
Section: Introductionmentioning
confidence: 99%
“…Although mortality rates can be lowered significantly by early diagnosis and ensuing therapy, the vital risk of transplantation-related acute toxoplasmosis warrants prophylactic drug treatment in stem cell recipients [5] .…”
Section: Introductionmentioning
confidence: 99%
“…Common neurologic complications are infections, including toxoplasmosis. Recent studies showed that toxoplasma disease may develop from 0.25-4% allotransplant recipients, with a mortality rate as high as 60-90% [3,4,9,10,11,12,13]. PCR techniques have been developed for noninvasive diagnosis, also in cerebral toxoplasmosis, which contribute to rapid diagnosis and monitoring of treatment efficacy [1,2,9,10,11,13,14,15,16].…”
Section: Discussionmentioning
confidence: 99%
“…Some authors, however, still emphasize the role of serology in the diagnostics of toxoplasmosis, as well as a combination of serology and PCR techniques [9,11]. Serological tests are very useful before transplantation to assess serostatus of the recipient and donor, and for monitoring the recipient after transplantation [11,13].…”
Section: Discussionmentioning
confidence: 99%